The Constitutionality of Restrictions on Freedom of Expression in the Digital Era: An Analysis of Constitutional Court Decisions - Hermanto; Rhogust, Muhammad; Endah Lestari, Martanti; Bahri, Syaiful (Yayasan Pendidikan Belajar Berdikari, 2022)
The rapid evolution of digital communication has redefined the scope and limits of constitutional freedoms particularly the right to freedom of expression. In Indonesia, this right—enshrined in Articles 28E(3) and 28F of the 1945 Constitution—faces new challenges arising from the expansion of online speech and state regulation under the Electronic Information and Transactions Law (UU ITE). This study examines the constitutionality of restrictions on freedom of expression within Indonesia’s digital landscape through a doctrinal and case-based analysis of key Constitutional Court decisions, including Decisions No. 50/PUU-VI/2008, No. 2/PUU-VII/2009, No. 82/PUU-XII/2014, and No. 76/PUU-XV/2017.Findings reveal that the Constitutional Court consistently applies the principle of proportionality as the central test for evaluating the legitimacy of expression-related restrictions. The Court’s reasoning reflects an ongoing effort to harmonize domestic constitutional provisions with international human rights standards, particularly Article 19 of the International Covenant on Civil and Political Rights (ICCPR). While the UU ITE remains constitutionally valid, the Court has emphasized the need for legislative refinement to prevent vague or overly broad interpretations that could infringe upon democratic freedoms.The analysis further highlights that the digital era demands adaptive constitutional interpretation capable of reconciling technological innovation with enduring democratic principles. The Constitutional Court’s jurisprudence demonstrates that constitutional democracy in the digital age must be both protective and responsive—safeguarding individual liberty while ensuring that digital governance serves the public interest. Ultimately, this study underscores the Court’s pivotal role in shaping Indonesia’s constitutional evolution toward a rights-centered model of digital governance, ensuring that constitutional freedoms remain robust amid technological transformation.